Spindle Cell Melanoma Presenting as an Ulcer in a Black Diabetic - Gaskin, P. S.; Depeiza, N.; Brathwaite, D.; Gaskin, D. A.; Ward, J. (Case reports in pathology, 2020)
Background. Melanoma in blacks is uncommon and exceedingly rare in association with a diabetic ulcer. We present a case of a spindle cell melanoma masquerading as a diabetic ulcer. Case Report. A 57-year-old overweight woman presented to The Maria Holder Diabetes Centre for the Caribbean with a nonhealing ulcer of the right heel after being treated by various primary care physicians over the preceding year. Her general and systematic examinations were unremarkable. There was a 1×1.5 cm ulcer with a necrotic base which bled easily on contact with no evidence of peripheral neuropathy nor arterial insufficiency. Microscopic examination of a biopsy of the lesion showed fascicles of spindle cells with plump nuclei and intracytoplasmic yellow-brown pigment. Immunohistochemistry confirmed a diagnosis of melanoma. Discussion. There should be a high index of suspicion of malignancy with nonhealing diabetic ulcer especially when coupled with short disease duration. This case highlights the importance of a biopsy and histological evaluation in ulcers presenting in recently diagnosed diabetics with no evidence of peripheral neuropathy or vascular disease. Melanoma should be considered in spindle cell lesions especially with pigment and residual nevus cells.